Teachers’ Beliefs and Views on Grade Inflation in the Algerian Universities - ROUAI, Ghezala (My University, 2020)
Grade inflation is commonly known as giving students higher grades without an increase in their performance. Grade inflation has become a sensitive topic in the field of education. Thus, it is widely debated among scholars since it affects the students' career. Many studies were conducted concerning the issue of grade inflation in higher education but few (not to say any) were carried on grade inflation in the Algerian higher educational context. This study aims to explore the beliefs and views of Algerian university teachers regarding the issue of grade inflation. The study used a questionnaire designed to twenty EFL teachers (working in different universities) in order to quantitatively and qualitatively check their opinions about the existence of grade inflation at their departments as well as their causes and consequences. The findings reveal that most of teachers believe that grade inflation exists to some extent in their departments. In addition, the main reason of inflating grades is considering students' failure. As for their beliefs regarding the consequences, the participants agreed that the main consequences of grade inflation are deteriorating the work ethics of students and causing grades to fail their positive functions of providing feedback on students' performance.
Keywords: Grade inflation; Teachers’ beliefs; English department; Algerian University